Is Commerce Good for the Soul? An Empirical Assessment. (18th October 2018) - Wright, Walker A.
Abstract: Numerous empirical studies suggest that market exchange helps (a) create the conditions for liberal values to flourish, (b) refine our sense of fairness, (c) promote cooperation with those who are different from ourselves, (d) develop networks of mutual trust and trustworthiness, (e) generate tolerance and respect towards others, and (f) undermine hostility and conflict in favour of peace. This article reviews this empirical evidence and argues that markets make us better people, morally speaking.